2008
DOI: 10.1021/jm800200u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of d-Amino Acid Oxidase Inhibitors

Abstract: D-amino acid oxidase (DAAO) catalyzes the oxidation of D-amino acids including d-serine, a full agonist at the glycine site of the NMDA receptor. A series of benzo[ d]isoxazol-3-ol derivatives were synthesized and evaluated as DAAO inhibitors. Among them, 5-chloro-benzo[ d]isoxazol-3-ol (CBIO) potently inhibited DAAO with an IC50 in the submicromolar range. Oral administration of CBIO in conjunction with d-serine enhanced the plasma and brain levels of d-serine in rats compared to the oral administration of d-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
117
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 16 publications
12
117
2
Order By: Relevance
“…A number of recent studies focused on the development of new and effective hDAAO inhibitors as a treatment strategy for schizophrenia by modulating D-serine concentrations in the brain. [10][11][12][13] These studies reported on the synthesis and identification of new hDAAO inhibitors (mainly aromatic compounds that bind in the hDAAO active site, for a structural comparison see Ref. 13) and on their effect on rat brain D-serine concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies focused on the development of new and effective hDAAO inhibitors as a treatment strategy for schizophrenia by modulating D-serine concentrations in the brain. [10][11][12][13] These studies reported on the synthesis and identification of new hDAAO inhibitors (mainly aromatic compounds that bind in the hDAAO active site, for a structural comparison see Ref. 13) and on their effect on rat brain D-serine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, and in agreement with the aforementioned model, hDAAO is now considered the target for a new class of drugs (hDAAO inhibitors) to treat schizophrenia. [10][11][12][13] Human DAAO shows the main properties of the dehydrogenase-oxidase class of flavoproteins and shares a low turnover number and a ternary complex (sequential) kinetic mechanism with pig kidney DAAO (pkDAAO, %85% sequence identity). 7 Indeed, this human flavoenzyme can be distinguished from the other known DAAOs because it is a stable homodimer even in the apoprotein form, because the binding of the FAD cofactor is the weakest among the known DAAOs (K d value is in the micromolar range) 1,7 and because it specifically interacts with pLG72 (which is expressed on primates only).…”
Section: Introductionmentioning
confidence: 99%
“…D-Alanine (100, 300 or 1000 mg/kg, Wako Pure Chemical Industries, Ltd., Tokyo, Japan), dissolved in 0.5% carbomethoxycellulose (CMC: Wako Pure Chemical Co., Tokyo, Japan), was administered orally in a volume of 10 ml/kg. CBIO (30 mg/kg) [34,35] was suspended in 0.5% CMC, was administered orally in a volume of 10 ml/kg. The other chemicals used were purchased from commercial sources.…”
Section: Drugs and Drug Administrationmentioning
confidence: 99%
“…Recently, we reported that oral administration of the novel and potent DAAO inhibitor, 5-chloro-benzo[d]isoxazol-3-ol (CBIO) (Fig. 1), in conjunction with D-serine could enhance the plasma and brain levels of D-serine in rats and mice compared to the oral administration of D-serine alone [34,35]. The IC 50 value of CBIO for DAAO was 188 nM [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that treatment of schizophrenia patients with D-serine, a co-agonist of the N-methyl-D-aspartate (NMDA) receptor, improved symptoms when administered in combination with antipsychotics (6,7). Therefore, much attention has recently been focused on the inhibition of DAO, which decomposes endogenous D-serine in vivo, and selective DAO inhibitors have been developed and investigated by pharmaceutical company research groups (8)(9)(10). Despite this research focus on DAO inhibition, the primary pharmacological action of most institutionally prescribed antipsychotics is the blockade of dopamine D2 and serotonin receptors (2); however, these drugs might also inhibit DAO activity in vivo.…”
Section: Introductionmentioning
confidence: 99%